Ecology and rapid detection of diatom pseudo-nitzschia (bacillariophyceae) in Kuching estuaries - Wang, Chuan Yu (Universiti Malaysia Sarawak (UNIMAS), 2012)
Phytoplankton plays an important role in aquatic ecosystem and serves as sources of foods to support high trophic level in food chains. However, some of the phytoplankton is capable of producing bioactive compound which is harmful to other aquatic organisms. Several species in the genus of Pseudo-nitzschia have been known to produce neurotoxin, domoic acid (DA). In this study, field sampling was conducted fortnightly started from September 20 II to April 2012 to study distribution of genus Pseudo-nitzschia in Kuching estuary water. Abundance of cells was low throughout the study period with exception of April. Pseudo-nitzschia cell isolated from Samariang was successful growth in culture tube and was identified as P.brasi/iana after observed through TEM. The molecular approach Whole-cell fluorescence in situ hybridization (FISH) was developed to detect Pseudo-nitzschia species. The in siJ/ico oligo nucleotide probe was designed for P. pungens (L-S-Ppun-405-A-18), P. circumpora (L-S-P-Cirm-62-A-18), and P. cacianta (L-S-P-cacian-63-A-25) based on sequences obtain in this study and sequences retrieved from SILVA data base. The designed L-S-Ppun-405-A-18 for P.pungens was synthesized with FITC labeled and optimization was carried out for this particular probe. The L-S-Ppun-405-A-18 probe was applied on cultured and spiked samples with UniC and UniR probe as control. The probe showed high specificity toward P. pungens. This study showed FISH is a more reliable in the rapid detection Pseudo-nitzschia cells in HABs monitoring.